Teacher Preparedness in Utilizing Technology for Learning: Navigating Challenges and Opportunity in the Digital Age - Fawziyah, Dhini Alvina (Universitas Kapuas, 2025)
This study examines the extent of teacher preparedness in integrating technology into learning by English as a Foreign Language teachers in the current digital era. The difficulties teachers face when using technology such as inadequate infrastructure, lack of training, and technical barriers form the basis of this study. Seven teachers from different levels of education participated in semi-structured interviews to provide data for a descriptive qualitative approach. Results show that the majority of teachers view technology positively, especially in terms of improving teacher engagement and relationships with students. However, there are still some significant issues, such as students' insufficient digital literacy, lack of technical assistance, and limited internet connection. Teachers' age and tendency to use conventional teaching approaches also affect to teacher prepaedness. This study shows that greater access to digital resources and thorough training are needed, even though teachers are more interested in using technology. According to the findings of this study, technology has a lot of potential to improve learning standards provided that current barriers can be removed with the help of adequate infrastructure support and training.